A two-step approach to predict shear band development with crystal plasticity finite element method (CPFEM). (1st October 2016) - Wu, Yurui; Shen, Yao; Wu, Peidong; Chen, Kaiguo; Yu, Yuying; He, Guo
Abstract: A two-step approach is proposed to investigate the shear band formation in cold-rolled aluminum alloy sheet during plane strain tension, compression and simple shear tests. In the first step, a finite element model with only one element using Taylor type polycrystal plasticity model is applied to compute the stress-strain curve of the deformation. In the second step, a full scale mesoscopic simulation is applied for a further study of the details of the shear band development for cases with higher possibility of shear band formation as judged from the results in step 1. Systematic studies show that the hardening/softening features of stress-strain curves obtained by one-element method well agree with the extent of macroscale shear bands development in mesoscopic scale simulation: softening or flat stress-strain curves correspond to the formation of severe macroscale shear band in mesoscopic scale simulation, and the stronger the softening is, the more severe the macroscale shear band is, whereas no macroscale shear band is developed when the curves exhibit continuous and obvious hardening. Therefore, when it is needed to investigate probability and features of shear band formation in many samples or loading modes, e.g. loading along different directions, people can use the first step to efficiently estimate the possibility of macroscale shear band development for all the cases concerned, and then apply the full scale mesoscopic simulation only for those cases where stress-strain curves exhibit little hardening or softening features. Our calculations show that the computation efficiency can be substantially improved by the two-step approach.